Examining the dependence of macroplastic fragmentation on coastal processes (Chesapeake Bay, Maryland). (August 2021) - Rizzo, Marzia; Corbau, Corinne; Lane, Benjamin; Malkin, Sairah Y.; Bezzi, Virginia; Vaccaro, Carmela; Nardin, William
Abstract: Plastic debris in the coastal environment is subject to complex and poorly characterized weathering processes. To better understand how key environmental factors affect plastic degradation in a coastal zone, we conducted an in situ experiment. We deployed strips of high density polyethylene (HDPE) and polystyrene (PS) in paired coastal areas of contrasting conditions (hydrodynamic activity: erosional or depositional; water depths: subtidal or intertidal). Strips were collected after environmental exposures at 4, 8, and 43 weeks and analyzed for change in mass, algal biofilm growth, and imaged by petrographic and electron microscopy (SEM-EDS). Significant surface erosion was evident on both polymers, and was more rapid and more extensive with PS. Degradation of PS was responsive to intensity of hydrodynamic activity, and was greater at intertidal depths, highlighting the critical role played by photo-oxidation in the coastal zone, and suggesting that algal biofilms may slow degradation by playing a photo-protective role. Highlights: Degradation of PS was faster than HDPE at all deployment locations. Numerous grooves and pitting indicated surface weathering of HDPE. PS surface weathering and fragmentation was strongly responsive to coastal exposure. Significantly greater degradation of PS under erosional and intertidal conditions. Greater biofilm development at subtidal depths, regardless of plastic type.